Reactivity of Indolylmethylacetates with N, O, and S Soft Nucleophiles: Evidence of 2‐Alkylideneindolenines and 3‐Alkylideneindoleninium Generation by ESI‐MS and IRMPD Spectroscopy. Issue 43 (16th November 2022) - Arcadi, Antonio; Berden, Giel; Ciogli, Alessia; Corinti, Davide; Crestoni, Maria Elisa; De Angelis, Martina; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia; Marrone, Federico; Marsicano, Vincenzo; Oomens, Jos; et al.
Abstract: The synthesis of (aminomethyl), (tosylmethyl), and (aryloxymethyl) indoles starting from indolylmethylacetates and N, O, and S soft nucleophiles has been developed. ESI‐MS and IR multiple‐photon dissociation (IRMPD) spectroscopy analyses confirm the reaction proceeds through a conjugate addition of the nucleophile to 2‐alkylideneindolenines and 3‐alkylideneindoleninium. Abstract : The synthesis of (aminomethyl), (tosylmethyl), and (aryloxymethyl) indoles starting from indolylmethylacetates with various nucleophiles has been developed. The experimental evidence of the in situ generation of 2‐alkylideneindolenines and 3‐alkylideneindoleninium as reaction intermediates has been provided through ESI‐MS and IRMPD spectroscopy analysis.